Znaczenie rzeczownika φθόνος w Mdr 2,24 - Zieliński, Marcin (The Biblical Annals, 2021)
The interpretation of the noun φθόνος in Wis 2:24 may raise some difficulties. In exegesis, φθόνος is generally referred to the attitude of the devil who, jealous of man, rebelled against God. This meaning already appears in apocryphal and patristic literature. This article presents the context of the analyzed verse, issues related to its translation, and possible interpretations. First, it explores the nature of death, then tries to show what reality is behind the term διάβολος and why the author describes his action as motivated by envy. Based on the texts of Philo of Alexandria, the article argues that envy, understood as sadness related to the lack of various goods that others have, is only a definition of the essence of this feeling. It seems that the inspired author primarily wanted to show envy as a negative attitude, radically opposed to the idea of ​​wisdom, virtue and closeness to God. In such an interpretation, envy reveals a state of moral evil, an absolute lack of wisdom, which results in separation from God, causes discord between people, and ultimately leads to spiritual death.